What contributes the most to the breast cancer patients’ quality of life during the therapy - clinical factors, functional and affective state or social support? - Novakov Ivana; Popović-Petrović Svetlana; Ilinčić-Zlatar Sonja; Tatić Milanka; Ševo Mirjana (Vojnosanitetski Pregled)
Background/Aim. As significant advances in cancer treatment have occurred over the past decades, the crucial questions in oncology nowadays are not related only to the treatment of the illness but also to the quality of life (QOL) of patients. The aim of our study was to explore which set of determinants (clinical, functional, affective, or social) has the greatest impact on explaining QOL in women who live with the diagnosis of breast cancer. Methods. The research was conducted on 64 women (with a mean age of 58.36 ± 11.30) while undergoing radiation therapy at the Oncology Institute of Vojvodina, Serbia. Quality of Life Instrument – Breast Cancer Patient Version (QOL-BC) questionnaire was used for evaluation of physical, psychological, social, spiritual, and general well-being, the Upper Extremity Functional Index (UEFI) was applied for the assessment of the upper extremity function, the Depression, Anxiety, and Stress Scale-21 Items (DASS-21) was used for measuring symptoms of depression, anxiety, and stress, the Medical Outcomes Survey, Social Support Survey (MOS-SSS) served for evaluation of social support; demographic and clinical data of patients were also collected. Results. Analysis of Variance (ANOVA) with repeated measures [F(2.03, 127.80) = 20.24, p < 0.001] showed that in our sample, physical QOL was significantly better from all other domains, while social QOL was significantly lower from both physical and psychological aspect. A hierarchical regression analysis [F(8, 55) = 7.16, p < 0.001, R2 = 0.51] showed that patients who received adjuvant chemotherapy and experienced high levels of stress and poor social support usually had diminished general QOL. Introduction of affective-related variables [ΔR2 = 0.16, p(ΔF) < 0.01] and social support [ΔR2 = 0.05, p(ΔF) < 0.05] led to a significant increase in proportion of explained variance over and above the clinical and functional variables. Conclusion. Our results indicate that psychological and social resources are more important in predicting QOL compared to clinical and functional factors. At the same time, the social, psychological, and spiritual well-being of patients is significantly worse compared to the physical QOL, meaning that there is still much left to be done regarding the progress from a purely somatic to a holistic approach in the treatment of breast cancer.